Achieving two things at one stroke: crystal engineering simultaneously optimizes the emission and mechanical compliance of organic crystals. Issue 10 (18th February 2022) - Tang, Baolei; Li, Mengjuan; Yu, Xu; Zhang, Hongyu
Abstract : Two organic polymorphs with totally different emission and mechanical properties have been designed based on a single benzene emitter. The elastically bendable and plastically twistable polymorph displays lasing potential with CIE y < 0.03. Abstract : Optimizing the molecular arrangements of organic crystalline materials towards desired luminescence can avoid complex chemical synthesis and laborious purification. Very recently, the poor mechanical compliance, being a notorious bottleneck in crystal application for a long time, has been reported to be solvable through precisely controlling the molecular packing structures and intermolecular interactions. However, simultaneously regulating the luminescence and mechanical properties of organic crystals from the perspective of supramolecular optimization for advanced materials remains a big challenge. By employing a commercially available single-benzene emitter, here we report two organic polymorphs that display completely different luminescence and mechanical properties. The critical factors dominating the emission and mechanical compliance have been perfectly disclosed based on careful analyses of the crystal structures of two polymorphs. The blue emissive polymorph underwent elastically bent and plastically twisted deformations upon applying a transverse force and a twisting force, respectively. To demonstrate the application of these elegant organic crystals, they were tested as flexible lasing media and found to generate amplified spontaneous emission with CIE y < 0.03 even in a highly twisted state. The success in achieving a flexible deep blue organic laser is expected to make a breakthrough for the future wearable optoelectronic technology. In addition, this study, in a broad sense, breaks the boundaries of regulating the optical and mechanical properties of organic materials by crystal engineering.